2017
DOI: 10.1073/pnas.1703559114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing drives acuity of αβ T-cell recognition

Abstract: T lymphocytes use surface αβ T-cell receptors (TCRs) to recognize peptides bound to MHC molecules (pMHCs) on antigen-presenting cells (APCs). How the exquisite specificity of high-avidity T cells is achieved is unknown but essential, given the paucity of foreign pMHC ligands relative to the ubiquitous self-pMHC array on an APC. Using optical traps, we determine physicochemical triggering thresholds based on load and force direction. Strikingly, chemical thresholds in the absence of external load require orders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
197
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(213 citation statements)
references
References 83 publications
11
197
0
2
Order By: Relevance
“…In summary, although forces are likely to be generated at the contact interface, mechanisms may be operating to reduce the tension on the TCR/pMHC interaction. Although beyond the scope of this review, it has been suggested that applied forces on the TCR may be required to induce TCR signaling, but there is also evidence that TCR signaling can take place without pMHC ligands and hence an applied force . The role of force in mechanically transducing signals is beyond the scope of this work and we refer the reader elsewhere…”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%
“…In summary, although forces are likely to be generated at the contact interface, mechanisms may be operating to reduce the tension on the TCR/pMHC interaction. Although beyond the scope of this review, it has been suggested that applied forces on the TCR may be required to induce TCR signaling, but there is also evidence that TCR signaling can take place without pMHC ligands and hence an applied force . The role of force in mechanically transducing signals is beyond the scope of this work and we refer the reader elsewhere…”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%
“…The connection of TCR components to the actin filaments inside microvilli also allows T cells to exert significant forces on these components during the first few seconds following encounter of the APC, and these forces may stabilize the TCR-MHC-peptide bonds, as suggested by recent biophysical measurements (77)(78)(79)(80). As the T cell interaction with the APC persists, the phosphorylated ERM linkers become inactivated by dephosphorylation (63) and release the connection of the cortical actin cytoskeleton and the plasma membrane in the vicinity of the TCR machineries.…”
Section: Discussionmentioning
confidence: 99%
“…Observing mechanotransduction in the immune system is more complex than in adherent cells; however, recent technological advances have enabled scientists to directly measure forces exerted by leukocytes during an immune repsonse. 165,166 It is becoming evident that external forces are sensed by lymphocytes during activation and inhibition at the IS, and these are converted into biochemical signals that impact the immune response. Often, it is the cytoskeleton that mediates between external physical stimuli and signaling pathways.…”
Section: Discussionmentioning
confidence: 99%